The Influence of Internal Control and Individual Morality on Fraud Prevention in Industrial Garment Company - Azhari, Farida; Bayunitri, Bunga Indah (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2025)
The purpose of this study is to ascertain whether fraud prevention at CV X, Bandung Regency, is impacted by internal control and personal ethics. Internal control and personal morality are the independent variables that are being examined in this study. Preventing fraud is the dependent variable. The quantitative descriptive approach method is the research methodology employed in this study. The study's population consisted of 58 workers at CV X Kab. Bandung. The census method with purposive sampling was the sample strategy employed in this investigation. 58 employees of CV X Kab. Bandung serve as the research's sample size. At a significance level of 5%, multiple linear regression analysis is the analysis approach employed in this study. Based on the results of the study, it shows that internal control, individual morality on fraud prevention at CV X Kab.bandung included in the good category. Besides that partial research results (t test) show that internal control affects fraud prevention in CV X Kab.bandung and individual morality affects fraud prevention in CV X Kab.bandung.